The following series and integrals relate log(2) to its third and fourth convergents, $\frac{2}{3}$ and $\frac{7}{10}$.

$$\begin{align} \log\left(2\right)-\frac{2}{3} &= \sum_{k=1}^\infty \frac{1}{(2k+1)(2k+2)(2k+3)}\\ &= \int_0^1\frac{x^2(1-x)^2}{1+x^2}dx\\ &= \frac{1}{2}\int_0^1 \frac{x^2(1-x)}{1+x}dx \\ \\ \frac{7}{10}-\log\left(2\right) &= \sum_{k=2}^\infty \frac{1}{(2k+2)(2k+3)(2k+4)} \\ &= \int_0^1\frac{x^4(1-x)^2}{1+x^2}dx\\ &= \frac{1}{2}\int_0^1 \frac{x^5(1-x)}{1+x} dx \\ &= \frac{24}{5}\sum_{k=0}^{\infty} \frac{1}{(4k+2)(4k+3)(4k+4)(4k+5)(4k+6)} \\ &= \frac{1}{5}\int_{0}^{1} \frac{x(1-x)^4}{1-x^4}dx = \frac{1}{5}\int_{0}^{1} \frac{x(1-x)^3}{(1+x)(1+x^2)}dx \\ \end{align} $$

Similarly, for $\log(3)$ and $\log(5)$, we have

$$\begin{align} \log(3)-1 &= \sum_{k=0}^\infty \frac{2}{(3 k+2) (3 k+3) (3 k+4)} \\ &= \int_{0}^{1} \frac{x(1-x)^2}{1-x^3}=\int_{0}^{1} \frac{x (1-x)}{1+x+x^2} dx \\ \\ \frac{11}{10}-\log(3) &= \sum_{k=1}^{\infty} \frac{8}{(3k+1)(3k+2)(3k+3)(3k+4)(3k+5)} \\ &= \frac{1}{3}\int_{0}^{1} \frac{x^3(1-x)^4}{1-x^3}=\int_{0}^{1} \frac{x^3 (1-x)^3}{1+x+x^2} dx \\ \log(5)-\frac{3}{2} &= \sum_{k=0}^\infty \left(\frac{8}{(5k+3)(5k+5)(5k+7)}+\frac{2}{(5k+4)(5k+5)(5k+6)} \right) \\ \end{align}$$

Q Is there a similar integral for $\log(5)-\frac{3}{2}$?


Extending the method used by Olivier Oloa on the series for $\log(2n+1)-H_n$, one gets the following Dalzell-type integrals

$$\log(7)-\frac{11}{6}=\int_0^1 \frac{x^3 (1-x) (1+3 x+6 x^2+3 x^3+ x^4)}{1+x+x^2+x^3+x^4+x^5+x^6} dx$$ check

$$\log(9)-\frac{25}{12}=\int_0^1 \frac{x^4 (1-x) (1+3 x+6 x^2+10 x^3+6 x^4+3 x^5+x^6)}{1+x+x^2+x^3+x^4+x^5+x^6+x^7+x^8} dx$$


The terms in the larger polynomial in the numerator are $\frac{(n+1)(n+2)}{2}x^n$ in the first half and then mirror.

In general, $$\log(2n+1)-H_n=\int_{0}^{1} \frac{x^n(1-x)}{\sum_{k=0}^{2n}x^k} \left( \frac{n(n+1)}{2}x^{n-1}+\sum_{k=0}^{n-2}\frac{(k+1)(k+2)}{2}\left(x^k+x^{2(n-1)-k}\right)\right)dx$$

This integral proves $$\log(2n+1)>H_n$$ which agrees with $$\lim_{n->\infty} (log(2n+1)-H_n)=\log(2)-\gamma$$


By using a partial fraction decomposition of the summand, you get $$ \begin{align} \log(5)-\frac{3}{2}&=\sum_{k=0}^\infty \left(\frac{8}{(5k+3)(5k+5)(5k+7)}+\frac{2}{(5k+4)(5k+5)(5k+6)} \right)\\\\ &=\sum_{k=0}^\infty \int_0^1 \left(x^{5k+6}+x^{5k+5}+x^{5k+3}+x^{5k+2}-4x^{5k+4}\right)dx\\\\&=\int_0^1 \sum_{k=0}^\infty \left(x^{5k+6}+x^{5k+5}+x^{5k+3}+x^{5k+2}-4x^{5k+4}\right)dx \end{align} $$ that is

$$ \log(5)-\frac{3}{2}=\int_0^1 \frac{x^2(1-x)(1+3x+x^2)}{1+x+x^2+x^3+x^4}\:dx. $$

  • 1
    $\begingroup$ Olivier: are you sure of your result? For me, your integral isn't convergent wolframalpha.com/input/?i=integrate+from+x%3D0+to+1+x^2(5%2B5x-4x^2%2B5x^3%2B5x^4)%2F(5*(1-x^5))+dx $\endgroup$ – FDP Feb 16 '16 at 9:43
  • $\begingroup$ For me, it's $\displaystyle \int_0^1 \frac{x^2(1+x-4x^2+x^3+x^4)}{1-x^5}dx$ (found with PARI GP LLL Stuff, confirmed by Wolfram Alpha) $\endgroup$ – FDP Feb 16 '16 at 11:12
  • 1
    $\begingroup$ or $\displaystyle \int_0^1 \dfrac{x^2(x-1)^2(x^2+3x+1)}{1-x^5}dx$ showing the positivity of $\log(5)-\dfrac{3}{2}$ $\endgroup$ – FDP Feb 16 '16 at 11:53
  • $\begingroup$ @FDP Good catch! There was a wrong factor 1/5, thank you! $\endgroup$ – Olivier Oloa Feb 16 '16 at 20:38
  • $\begingroup$ @FDP Nice! Now the denominators for the integral of $log(n+1)$ are $\sum_{k=0}^{n} x^k$ and coefficients $1,1,1,1,-4$ agree with those in math.stackexchange.com/questions/883348/series-for-logarithms. But this is misleading because the exponents are not in order, $-4$ is the central one in this regrouping. In the numerator, beautiful symmetry in polynomial $(1+3x+x^2)$ that multiplies the same numerator as in the second integral for $\log(2)$, namely $x^2(1-x)$. $\endgroup$ – Jaume Oliver Lafont Feb 19 '16 at 5:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.